Prediction of Post spinal anesthesia hypotension in patients undergoing cesarean section using Perfusion index - Pyakurel, Kumud; Rajbanshi, Lalit Kumar; Bhattarai, Ramesh; Dahal, Sonia (Birat Journal of Health Sciences, 2020)
Introduction: Spinal anesthesia induced hypotension frequently complicates Cesarean delivery. This is usually due to sudden sympatholysis causing decreased venous return which can be aggravated by physiological changes of pregnancy leading to change in baseline peripheral vascular tone. Strategies to prevent hypotensive episodes should be the primary aim of anesthetic management. A simple noninvasive measurement of perfusion index derived from pulse oximeter predicting hypotension during the routine intraoperative course could provide a new dynamism to the management and improving the safe execution of anesthesia. Objectives: The primary objective of this study was to compare incidence of hypotension following SAB for LSCS in patients with baseline PI ≤ 3.5 to those with PI > 3.5. The secondary objectives were to compare PI, HR, SBP, MAP at various time intervals and also to study the side effects between the two groups. Methodology: This prospective observational study was conducted at Nobel Medical College Teaching Hospital from to July 2019 to October 2019. 73 Term parturients presenting for elective cesarean delivery were included for the study. Upon arrival in the operation room, standard monitors were attached and baseline HR, SBP, DBP, MAP, PI and SPO2 were recorded in supine position. The patients with baseline PI ≤ 3.5 were enrolled into Group I and those with a PI > 3.5 were enrolled into Group II. Spinal Anesthesia with 10mg of 0.5% heavy Bupivacaine and 20mcg Fentanyl ( total 2.4ml) was given at L3-L4 interspace in sitting position using midline approach. Patient was then returned to supine position with left lateral tilt of 15 degrees to facilitate left uterine displacement. Upper sensory level was checked at 5 minutes using alcohol swab. Once T-6 level was reached, surgery was started. Maternal SBP, DBP, MAP, HR and PI were recorded at 1 minute intervals between spinal injection and delivery and then 3 minutes until end of surgery. Clinically relevant hypotension was defined as the decrease in MAP by 20% or more from baseline value. Results: The incidence of hypotension in Group I was 18.8% (6/30) compared to 81.3% (26/38). This was clinically and statistically highly significant (P = 0.000, odds ratio 0.11). On Spearman’s rank correlation we found highly significant correlation between baseline PI >3.5 and number of episodes of hypotension (rs 0.482, P = 0.000). The sensitivity and specificity of baseline PI with cut-off 3.5 for predicting hypotension were 81.3% and 66.7% respectively. The ROC curve analysis showed 3.53 as appropriate cut‑off for our findings. The area under the ROC curve (AUC) was 0.734 [Figure 6](Lower bound 0.608 and upper bound 0.861, P=0.001). Conclusion : This study demonstrates that baseline PI of > 3.5 correlates with incidence of hypotension after spinal anesthesia for cesarean delivery in healthy parturients compared to a baseline PI of < 3.5.